Meeting future NOX emissions using an electric heater in an advanced aftertreatment system - Meruva, Prathik; Matheaus, Andrew; Sharp, Christopher A.; McCarthy, James E.; Collins, Thomas A.; Joshi, Ameya (Frontiers in Mechanical Engineering, 2022)
Engine and aftertreatment solutions are being identified to meet the upcoming ultra-low NOx regulations on heavy duty vehicles as published by the California Air Resources Board (CARB) and proposed by the United States Environmental Protection Agency (US EPA) for the year 2027 and beyond. These standards will require changes to current conventional aftertreatment systems for dealing with low exhaust temperature scenarios. One approach to meeting this challenge is to supply additional heat from the engine; however, this comes with a fuel penalty which is not attractive and encourages other options. Another method is to supply external generated heat directly to the aftertreatment system. The following work focuses on the later approach by maintaining the production engine calibration and coupling this with an Electric Heater (EH) upstream of a Light-Off Selective Catalytic Reduction (LO-SCR) followed by a primary aftertreatment system containing a downstream Selective Catalytic Reduction (SCR). External heat is supplied to the aftertreatment system using an EH to reduce the Tailpipe (TP) NOx emissions with minimal fuel penalty. Two configurations have been implemented, the first is a Close Coupled (CC) LO-SCR configuration and the second is an Underfloor (UF) LO-SCR configuration. The CC LO-SCR configuration shows the best outcome as it is closer to the engine, helping it achieve the required temperature with lower EH power while the UF LO-SCR configurations addresses the real-world packaging options for the LO-SCR. This work shows that a 7 kW EH upstream of a LO-SCR, in the absence of heated Diesel Exhaust Fluid (DEF), followed by a primary aftertreatment system met the 2027 NOx regulatory limit. It also shows that the sub-6-inch diameter EH with negligible pressure drop can be easily packaged into the future aftertreatment system.